ANALYSIS OF STUDENTS DIFFICULTIES IN SOLVING MATHEMATICAL PROBLEMS BASED ON HIGHER ORDER THINKING SKILLS FOR JUNIOR HIGH SCHOOL STUDENTS - Surlam, Ananda Eka Puspita; Chairuddin, Chairuddin; Tahir, Tahir (Universitas Sembilanbelas November Kolaka, 2025)
Higher-order thinking skills (HOTS) are essential in fostering students' critical and creative problem-solving abilities, particularly in mathematics. This study aims to determine the level of difficulty students face in solving HOTS-based mathematics problems. This qualitative descriptive study was conducted at SMPN 1 Latambaga with 23 eighth-grade students (class VIII A) as participants. The instruments, comprising tests and interviews, were constructed based on three indicators of HOTS: analyzing, evaluating, and creating. From the participants, six students were selected to represent three ability levels: high, moderate, and low. Students in the high category met all HOTS indicators. Moderate-level students achieved analyzing and evaluating but struggled with the creating aspect. Low-level students were only able to analyze and faced difficulties in evaluating and creating solutions. Their challenges included misapplication of principles, procedural errors, and verbal misunderstandings of question instructions. The findings highlight the need for targeted strategies to enhance students' critical and creative thinking in solving contextual and open-ended mathematics problems.